PERLINDUNGAN KONSUMEN TERHADAP PRODUK IKLAN KOSMETIK MENYESATKAN - Wiwik Sri Widiarty; Edy Kurniawan Tampubolon (to-ra, 2020)
The development of technology that is increasingly advanced now, especially with the trade of various imported products offered into the Indonesian Market through various media information, technology, and communication in the form of cosmetics product advertisements. Sales of goods / services through printed and electronic media, in all kinds of ways ranging from price discounts, to the lure of prizes up to hundreds of millions of rupiah, whose purpose is to attract consumers, so that many consumers are disadvantaged, because of the lure of cosmetic products the promised is not in accordance with its contents, due to the lack of transparency of the ads served, and consumers do not enjoy what is promised in the ad, because the producers violate the promised agreement, while the consumer has the right to get good, true, and honest information. Whereas manufacturers who are proven, offer, produce, advertise goods and / or services incorrectly, as regulated in Articles 9, 10, and Article 20 of Law Number 8 of 1999 Concerning Consumer Protection, will be subject to administrative sanctions in the form of compensation a maximum loss of two hundred million rupiahs, and a maximum of 5 (five) years imprisonment or a maximum fine of 2 (two) billion rupiahs.